2002
DOI: 10.4049/jimmunol.169.1.548
|View full text |Cite
|
Sign up to set email alerts
|

High Immunogenicity of Intracellular Myelin Oligodendrocyte Glycoprotein Epitopes

Abstract: Multiple sclerosis (MS) is an inflammatory and demyelinating disease of the CNS with associated axonal loss. There is strong evidence for an autoimmune pathogenesis driven by myelin-specific T cells. Myelin oligodendrocyte glycoprotein (MOG) induces a type of experimental autoimmune encephalomyelitis in animals which is very MS-like since there are demyelinating CNS lesions and axonal loss. This underscores the potential role of MOG in MS pathogenesis. We performed a T cell reactivity pattern analysis of MS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 44 publications
1
27
0
1
Order By: Relevance
“…However more recent data show that the intracellular part of MOG is much more immunogenic than the extracellular part. 44 In particular, there is a dominant MOG epitope recognized by CD4 þ T cells within the intracellular part of MOG comprising amino acids immediately flanking the 142 residue. The reported experiments were performed only with the more frequent V142 sequence.…”
Section: Involvement Of Mog In Ms Susceptibility S D'alfonso Et Almentioning
confidence: 99%
“…However more recent data show that the intracellular part of MOG is much more immunogenic than the extracellular part. 44 In particular, there is a dominant MOG epitope recognized by CD4 þ T cells within the intracellular part of MOG comprising amino acids immediately flanking the 142 residue. The reported experiments were performed only with the more frequent V142 sequence.…”
Section: Involvement Of Mog In Ms Susceptibility S D'alfonso Et Almentioning
confidence: 99%
“…Human recombinant MOG was expressed as previously described (22). Briefly, the DNA sequence encoding the extracellular domain of mature human MOG (including four N-terminal amino acids of the transmembrane domain) was PCR amplified and subcloned into pQ60 (Qiagen).…”
Section: Expression and Purification Of Mbp And Mogmentioning
confidence: 99%
“…As IFN-γ is still the most commonly measured Th1 cytokine (Hellings et al, 2001;Vergelli et al, 2001;Weissert et al, 2002) and has been shown to be involved in MS pathogenesis (Panitch et al, 1987;Woodroofe and Cuzner, 1993), we limited our results presented here to IFN-γ production by myelin-specific T cells. To avoid bias, analysis of the flow cytometrybased assay was performed without the evaluator knowing the patients' clinical status.…”
Section: Flow Cytometry-based Assaymentioning
confidence: 99%